WORK FROM HOME APPLICATION AND PROFESSIONALISM ON EMPLOYEE EFFECTIVENESS - Hesmita; Resty, Fenisi; Purwanto, Kelik (Jurnal Ekonomi dan Bisnis Airlangga, 2022)
Introduction: The Circular Letter of the Minister of PAN-RB No. 19 of 2020 concerning Adjustment of the Work System of State Civil Apparatus (ASN) in Efforts to Prevent Covid-19 in Government Agencies is intended as a guideline for Government Agencies in carrying out official duties by working at home for Apparatus State Civil Service as an effort to prevent and minimize the spread of Covid-19. This study aims to analyze and determine the effect of implementing Work From Home on the Work Effectiveness of Employees of the Department of Culture, Tourism, Youth and Sports, Dharmasraya Regency. Among other things, the purpose of this research is to analyze the effect of professionalism on the work effectiveness of employees at the Department of Culture, Tourism, Youth and Sports, Dharmasraya Regency. Methods: This study uses quantitative methods, and the sample in this study is 60 using non-probability sampling technique. Results: Work From Home has a significant effect in this study on the effectiveness of employees' work, and the Professionalism variable has a significant effect in this study on the effectiveness of employees' work. Work professionalism is based on effective and efficient principles that will improve employee performance. Conclusion and suggestion: For the Department of Culture, Tourism, Youth and Sports, Dharmasraya Regency needs to continue to improve the professionalism and work effectiveness of employees when doing the work that has been given, both when working from home or when working directly in the office in order to achieve the goals that have been set and that they can be implemented effectively and efficiently.